A Study on Changes in Equity Funds Due to Categorization of Mutual Funds and their Impact on Investors’ Behavior - Malar, Mercia Selva; Jose, Ann (Indian Journal of Research in Capital Markets, 2019)
Securities Exchange Board of India (SEBI), the regulator of the Indian capital markets, is constantly bringing in changes to improve investor experience in the capital markets. One such development is the October 6, 2017 announcement on the categorization of mutual funds to remove clutter in the industry and to make it more understandable to ordinary investors. The categorization caused a huge impact on the existing schemes and influenced investors to make necessary adjustments to their existing investments in mutual funds. The study used both primary and secondary data to analyze the impact of the changes on investors and their consequent behavior. The study was conducted as a descriptive and exploratory study. The study found that most mutual fund investors were aware of the changes and understood the changes and their impact. There were 11 mutual fund schemes, which had an impact on their attributes because of the categorization announcement of SEBI.